Microstructural and mechanical characterizations of steel tubes joined by transient liquid phase bonding using an amorphous Fe-B-Si interlayer - Di Luozzo, Nicolás (2014)
In this work the transient liquid phase bonding process was successfully used to join seamless carbon steel tubes using an amorphous Fe–B–Si foil as interlayer. The tubes were aligned with their butted surfaces in contact with the interlayer and the entire assembly was heated by means of an induction furnace under a reducing atmosphere. The temperature was raised to the process temperature (≈1300 °C) and then held for 7 min. The joining process was performed under a pressure of 5 MPa. The joined tubes microstructures were characterized by direct observations – scanning electron microscopy – and diffraction techniques – electron backscatter diffraction. Chemical analysis was performed by electron probe microanalysis. The joint region (JR) presents only ferrite grains - in contrast with the heat affected zone (HAZ) and the base metal (BM), whose microstructures consist of ferrite and cementite. Si content at the JR was precisely determined by chemical profiling, showing higher concentrations of Si compared with the HAZ and BM. These results are in accordance with the fact that the cementite is unable to form in Si enriched zones. Also, ferrite grains at the JR present high-angle grain boundaries with respect to the grains of the HAZ. Tensile tests show that the joined tubes failed away from the bond, at the HAZ, and reached 96% of the ultimate tensile strength of the BM, in the as-bonded condition. Microindentation hardness profiles across the bonding zone are in agreement with the observed microstructures at the different zones of the bond region.